Representation of National and Cultural Identity in Hungarian Translation of E. Vodolazkin’s Novel “Laurus” - M. A. Lappo; I. Pozsgai (Научный диалог)
The problem of translation of a literary text is considered, in which the interpretation of the national-cultural self-identification of the characters and the narrator is a significant tool for identifying its semantic dominant. For the first time, the issue of translation strategies in relation to the actualization of “one’s own and someone else’s” is studied on the material of the Hungarian translation of Evgeny Vodolazkin’s novel “Laurus”. The object of the study is archaic or non-archaic fragments of the Old Russian text in the speech of the heroes of the novel, as well as translations of personal names and toponyms. It is established that Lajos Palfalvi uses the translation strategy of domestication. The language means of archaization used in the translation text are described. It is proved that the leading means of archaization in translation is the use of the ancient Hungarian narrative past, other means of archaization are obsolete forms, words and syntactic constructions, rare words and words belonging to a high, literary or folk style. The adequacy of the translation strategy is demonstrated: these linguistic means refer the Hungarian reader to the Middle Ages, which corresponds to the author's intention. At the same time, it is noted that the specific linguocultural continuity of the Eastern Slavs (inhabitants of Ancient Russia) and Russians (native speakers of the modern Russian language) is only partially updated in the translation of the novel.